To the 40th anniversary of Kuban subtropical botanical garden - Isaenko Tatyana (Hortus Botanicus, 2017)
In the essay I share my memories not only of cooperation, but also of friendship with the director of the Subtropical botanical garden of Kuban, Doctor of Biological Science Karpun Yu. N., which lasts for almost 30 years. We know Yury Nikolaevich as a purposeful, talented scientist and as a sympathetic companion,who is ready to give a helping hand at any moment. Employees of the Stavropol botanical garden met Yury Nikolaevich not only at conferences in scientific institutions of the region, but also in the Kuban Subtropical botanical garden; he was a frequent visitor of our garden. As a result of experience and collection material exchange, we saw replenishment of gene pool of both organizations. I would like to wish good health and progress in his unusually interesting creativity to Yury Nikolaevich for many years from now on.